STUDENT'S MAJOR CONCENTRATION SELECTION SYSTEM USING WEB-BASED PROFILE MATCHING - Taufiq Ismail; Sri Winiarti; Rifki Pambudi (UNIVERSITAS STEKOM, 2021)
College students often select their major concentration area wrongly due to thoughtless considerations such as following their close classmates' choice. This may cause losses in time, effort, cost, and also mental energy. The research proposes a decision support system for selecting students' major concentration areas to solve students' problems in determining their study interest in informatics engineering. Profile Matching Method was chosen since it can sort out suitable study interest with students' criteria weight. The web-based decision support system was implemented using HTML, pure PHP programming languages with MySQL as its database. Boostrap and Javascript were added to enhance the web display; all application data will be saved in the hosting provider's web server. The application testing was done to 10 students as respondents in usability testing using Standardized Universal Percentile Rank-Questionnaire (SUPR-Q) for users and admins and User Acceptance Test (UAT). The conclusion was 70% compatibility of the students' major concentration area and the system's recommendation.